Using the theory of planned behavior to predict factors influencing fast-food consumption among college students - Maryam Sajjad; Afifa Bhatti; Barry Hill; Basem Al-Omari (BMC, 2023)
Abstract Purpose The purpose of this research is to examine the behavioral factors that impact fast food consumption (FFC) among college students in Pakistan by applying the theory of planned behavior (TPB). Methods Cross-sectional survey was distributed to college students in Pakistan. The questionnaire examines the factors associated with six categories: demographics, FFC pattern, intention for FFC, attitudes toward FFC, Subjective Norms (SN), and Perceived Behavioral Control (PBC). Data analysis was conducted using SPSS and SPSS AMOS software using descriptive statistics, inferential statistics (chi-square, t-test, Pearson correlation, and multiple regression analysis), and structural equation modeling (SEM) Analysis. Results A total of 220 questionnaires were completed (97 males and 123 females). There were significant differences in FFC association with gender. Among the constructs of TPB, behavioral intention (BI) and SN are the strongest predictors of the FFC (p < .05). TPB has significantly predicted FFC behavior with a variance of R2 0.603. The SEM analysis shows that the data collected were incompatible with the theoretical TPB model, making it unfeasible to test our five hypotheses or interpret the results due to the poor fit of the model with the data. Conclusions To ensure a good fit of the data with the specified TPB model in SEM analysis, the number of indicators should be limited (≤ 30), or the sample size should be greater (N ≥ 500). Pakistani college students' FFC is mainly influenced by friends and the increased popularity of fast food, despite their knowledge of its negative health effects. Educational programs should target specific harmful effects of fast food, and SN and BI are the strongest predictors of FFC among TPB constructs. These findings can be useful for developing targeted interventional health strategies and future research.